Revision of the genus Oxyscelio Kieffer (Hymenoptera, Scelionidae) from China - Mo, Wen-Hui; Chen, Hua-Yan; Johnson, Norman F.; Pang, Hong; Ma, Li; Liu, Jing-Xian (Zootaxa, 2020)
The genus Oxyscelio Kieffer from China is revised. Thirty-four species are recognized, of which two species are described as new: O. nullicarina Mo & Chen, sp. n., O. paracuculli Mo & Chen, sp. n., and fourteen species are newly recorded from China: O. aclavae Burks, O. arcus Burks, O. brevidentis Burks, O. excavatus (Kieffer), O. flabelli Burks, O. jaune Burks, O. kiefferi Dodd, O. labis Burks, O. mesiodentis Burks, O. mollitia Burks, O. nasolabii Burks, O. nubbin Burks, O. ogive Burks, and O. reflectens Burks. Keys to the Chinese species are provided.